Introductory Business Statistics - Tiemann, Thomas K.; Open Textbook Library (Minneapolis, MN Open Textbook Library, 2010)
The book "Introductory Business Statistics" by Thomas K. Tiemann explores the basic ideas behind statistics, such as populations, samples, the difference between data and information, and most importantly sampling distributions. The author covers topics including descriptive statistics and frequency distributions, normal and t-distributions, hypothesis testing, t-tests, f-tests, analysis of variance, non-parametric tests, and regression basics. Using real-world examples throughout the text, the author hopes to help students understand how statistics works, not just how to "get the right number."
1. Descriptive statistics and frequency distributions -- Descriptive statistics -- 2. The normal and t-distributions -- Normal things -- The t-distribution -- 3. Making estimates -- Estimating the population mean -- Estimating the population proportion -- Estimating population variance -- 4. Hypothesis testing -- The strategy of hypothesis testing -- 5. The t-test -- The t-distribution -- 6. F-test and one-way anova -- Analysis of variance (ANOVA) -- 7. Some non-parametric tests -- Do these populations have the same location? The Mann-Whitney U testTesting with matched pairs: the Wilcoxon signed ranks test. -- Are these two variables related? Spearman's rank correlation -- 8. Regression basics -- What is regression? -- Correlation and covariance -- Covariance, correlation, and regression
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks; Applied mathematics -- Textbooks; Statistics -- Textbooks